Daily patterns of clock and cognition-related factors are modified in the hippocampus of vitamin A-deficient rats - Golini, Rebeca Laura Susana (2012)
The circadian expression of clock and clock-controlled cognition-related genes in the hippocampus would be essential to achieve an optimal daily cognitive performance. There is some evidence that retinoid nuclear receptors (RARs and RXRs) can regulate circadian gene expression in different tissues. In this study, Holtzman male rats from control and vitamin A-deficient groups were sacrificed throughout a 24-h period and hippocampus samples were isolated every 4 or 5 h. RARα and RXRβ expression level was quantified and daily expression patterns of clock BMAL1, PER1, RORα, and REVERB genes, RORα and REVERB proteins, as well as temporal expression of cognition-related RC3 and BDNF genes were determined in the hippocampus of the two groups of rats. Our results show significant daily variations of BMAL1, PER1, RORα, and REVERB genes, RORα and REVERB proteins and, consequently, daily oscillating expression of RC3 and BDNF genes in the rat hippocampus. Vitamin A deficiency reduced RXRβ mRNA level as well as the amplitude of PER1, REVERB gene, and REVERB protein rhythms, and phase-shifted the daily peaks of BMAL1 and RORα mRNA, RORα protein, and RC3 and BDNF mRNA levels. Thus, nutritional factors, such as vitamin A and its derivatives the retinoids, might modulate daily patterns of BDNF and RC3 expression in the hippocampus, and they could be essential to maintain an optimal daily performance at molecular level in this learning-and-memory-related brain area.